Nano‐level position resolution for particle tracking in digital in‐line holographic microscopy. (3rd August 2015) - LEI, H.; HU, X.; ZHU, P.; CHANG, X.; ZENG, Y.; HU, C.; LI, H.; HU, X.
Summary: Three‐dimensional particle tracking in biological systems is a quickly growing field, many techniques have been developed providing tracking characters. Digital in‐line holographic microscopy is a valuable technique for particle tracking. However, the speckle noise, out‐of‐focus signals and twin image influenced the particle tracking. Here an adaptive noise reduction method based on bidimensional ensemble empirical mode decomposition is introduced into digital in‐line holographic microscopy. It can eliminate the speckle noise and background of the hologram adaptively. Combined with the three‐dimensional deconvolution approach in the reconstruction, the particle feature would be identified effectively. Tracking the fixed beads on the cover‐glass with piezoelectric stage through multiple holographic images demonstrate the tracking resolution, which approaches 2 nm in axial direction and 1 nm in transverse direction. This would facilitate the development and use in the biological area such as living cells and single‐molecule approaches.